Chế tạo vi điện cực sợi vàng ứng dụng cho phân tích lượng vết Hg(II) - Hải Yến, Phạm Thị; Thu Hà, Vũ Thị; Phong, Phạm Hồng (Vietnam Journal of Chemistry, 2016)
The present study has focused on manufacture of gold-wire microelectrode and attempt at using it in detection of Hg(II) by differential pulse anodic stripping voltammetry (DPASV) in electrolyte solution of 0.1 M NaNO3 + HNO3 pH = 3. The characteristic of quasi-steady state of the produced microelectrde was obtained with employing a redox Fe2+/Fe3+ couple in 0.1 M KCl solution. Obtained voltammograms showed the linear relation between the height of oxidation peak of pre-concentrated Hg at potential of 0.7 V and the concentration of Hg(II) in the bulk solution in the range of 1 ppb – 40 ppb with the coefficient efficiency (R2) of 0.995. The limit of detection was 0.056 ppb Hg(II). The error of 3 % was estimated after ten continuous measurements. Keywords. Gold wire microelectrode, mercury detection, trace concentration